Combining baseline characteristics to disentangle response differences to disorder-specific versus supportive psychotherapy in patients with persistent depressive disorder - Serbanescu, Ilinca; Walter, Henrik; Schnell, Knut; Kessler, Henrik; Weber, Bernd; Drost, Sarah Maria; Groß, Magdalena; Neudeck, Peter; Klein, Jan Philipp; Assmann, Nele; Zobel, Ingo; Backenstraß, Matthias; et al. (Behaviour research and therapy, 2020)
Does the pre-treatment profile of individuals with persistent depressive disorder (PDD) moderate their benefit from disorder-specific Cognitive Behavioral System of Psychotherapy (CBASP) versus supportive psychotherapy (SP)? We investigated this question by analyzing data from a multi-center randomized clinical trial comparing the effectiveness of 48 weeks of CBASP to SP in n = 237 patients with early-onset PDD who were not taking antidepressant medication. We statistically developed an optimal composite moderator as a weighted combination of 13 preselected baseline variables and used it for identifying and characterizing subgroups for which CABSP may be preferable to SP or vice versa. We identified two distinct subgroups: 58.65% of the patients had a better treatment outcome with CBASP, while the remaining 41.35% had a better outcome with SP. At baseline, patients responding more favorably to CBASP were more severely depressed and more likely affected by moderate-to-severe childhood trauma including early emotional, physical, or sexual abuse, as well as emotional or physical neglect. In contrast, patients responding more favorably to SP had a higher pre-treatment global and social functioning level, a higher life quality and more often a recurrent illness pattern without complete remission between the episodes. These findings emphasize the relevance of considering pre-treatment characteristics when selecting between disorder-specific CBASP and SP for treating PDD. The practical implementation of this approach would advance personalized medicine for PDD by supporting mental health practitioners in their selection of the most effective psychotherapy for an individual patient.
Available online 4 November 2019
Gesehen am 19.05.2020